KAUSALITAS HARGA SAHAM DAN KURS USD/IDR - Asep Risman (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
Theoretically Correlation exchange rate on stock prices, there is the relationship (negative) associated withthe performance of the issuer and economic conditions, there is also the approach that shows therelationship because of the behavior of foreign investors related to the investment portfolio, but there isalso approach that states no direct relationship. Likewise, previous studies showed a negative relationshipbeetween stock prices and exchange rates, but there is also research showing that the relationshipsignificant or under certain conditions, and the more extreme results showed no relationship betweenstock prices and exchange rates.In this study, we just want to prove which variable affect other variableswhether the exchange rate affect the price of the stock or just the opposite, based on test granger causality shows stock prices and the exchange rate of USD / IDR turns affect each other, so that the analysis ofchanges in exchange rates can be used to predict the tendency towards the stock price, and vice versa, inaddition to stock price changes are not necessarily directly affect the exchange rate at that time, but ittakes time or lag.